Street trees assessment in dowtown area of Santa Rosa, La Pampa (Semiárida, 2023)
Street tree can be defined as any tree planted within public sidewalks. The presence of urban street trees provides ecological, social and economic services that improve environmental conditions and life quality in cities. The objective of this study was to conduct an assessment of street trees in the downtown area of Santa Rosa. Survey was carried out between November 2020 and February 2021. This study examined the number, species, size and condition of street trees and recorded negative tree interactions with urban infrastructure in 498 blocks. Results comprise a total of 7381 records encompassing 84, 7 % trees, 9,9 % empty planters, 4,2 % shrubs, 0,3 % palms and 0,9 % herbs, grasses and other types. On average, there are 12 trees, 6 specimens of other types and 2 empty planters per block. The dominant species was the American ash (Fraxinus americana) with 50,5 % abundance. Sixty percent of trees were in the study área are in “very good” to “good” condition and the predominant tree size was medium (57,3 %). There is a minimum deficit of 1,851 trees, mainly noticeable in commercial fronts. Most of the negative interactions are observed on sidewalks, which are raised or broken due to the effect of tree roots. It is recommended to plant trees in order to increase the number of trees per block and complete empty planters. In addition, the extraction and replacement of specimens in poor condition should be facilitated. There is a need to develop lists with more suitable tree species, taking into account the characteristics of the area and the city, and including native species. This assessment provides a useful baseline for the effective management of urban street trees in Santa Rosa.
Keywords: Street trees, tree census, Santa Rosa.